Adverse Events of Concurrent Radiotherapy and ALK Inhibitors for Brain Metastases of ALK-Rearranged Lung Adenocarcinoma - NAKASHIMA, TAKAAKI (In Vivo, 2020)
Background: We investigated acute adverse events in patients with brain metastases (BMs) of anaplastic lymphoma kinase-rearranged (ALKr) non-small cell lung cancer (NSCLC) treated with both cranial radiotherapy and tyrosine kinase inhibitors (TKIs) of ALK. Patients and Methods: Acute AEs were retrospectively investigated in patients with BMs of ALKr-NSCLC who received both whole-brain radiotherapy (WBRT) and ALK-TKI. For comparison, they were also assessed in patients with epidermal growth factor receptor (EGFR)-mutated NSCLC and wild-type with neither ALK rearrangement nor EGFR mutation treated with WBRT. Results: Two ALKr cases were consequently eligible. Grade 3 otitis media unexpectedly occurred in both cases, while there was one case out of 11 and one case out of 18 of grade 2 otitis media among the EGFR-mutated cases and wild-type cases (p=0.013), respectively. Conclusion: Concurrent treatment with WBRT and ALK-TKI may be associated with acute severe ear toxicity in patients with BMs of ALKr-NSCLC.